Anthropology of the masquerade in the concept of Fyodor Stepun - Леховска , Марта (Философский полилог, 2021)
The article takes up the issue of the masquerade in an anthropological perspective. On the basis of F. Stepun’s letter to his wife (included in his work From the letters of an ensign artilleryman, 1916), in which the philosopher gives a characterization of the New Year as a holiday which inseparable attribute is the mask and masquerade (as a form of transgressing the individual self in the sphere of a culture), the author distinguishes the two types of this phenomenon – pure entertainment and philosophical or transcendental masquerade (these are Stepun’s terms). The paper explains what these terms mean in relation to the theatrical phenomenon and also draws a distinction between the mentioned secular holiday and religious holidays, for example Christmas Day and Feast of Holy Trinity. Then, in the light of the text The main problems of the theater (1923), the question about the conditions of the possibility of a philosophical masquerade is posed. Stepun, introducing the concepts of единодушие and многодушие, distinguishes three anthropological types – the city dweller, the mystic, and the artist; only one of them meets the conditions of philosophical masquerade. Thanks to the juxtaposition of these two mentioned above texts, the anthropological basis of the theatrical phenomena, including the masquerade, emerges. The article also raises the question of the tragic principle in the context of anthropology as well as culture. The similarity of the concepts of tragedy introduced by Fyodor Stepun and Vyacheslav Ivanov is shown. The final point of the considerations is the statement that refers the notion of theatricality first and foremost to an anthropological category, and only secondarily to cultural phenomena. The paper shows the necessary anthropological background for the phenomenon of masquerade.